Sustainable practices in the hotel sector: a literature review in Latin America. - Aguirre Zamora, Crystal Rubid; Sinforoso Martínez, Saulo (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2026)
OBJECTIVE: To analyze studies conducted in Latin America related to sustainable practice models in the hotel sector, with the purpose of recognizing approaches that drive environmental sustainability in these organizations.MATERIAL AND METHOD: This is a documentary research study with a descriptive scope. A literature review was conducted on 46 research papers from the last five years across various databases, including ResearchGate, Scielo, Redalyc, Dialnet, and indexed journals.RESULTS: The findings show that Mexico positions itself as one of the countries with the highest number of investigations in Latin America regarding sustainable practices. It recorded a total of 20 studies conducted between 2020 and 2025, representing a relative frequency of 43.4% out of 100%, highlighting its leadership in scientific production on sustainability.CONCLUSIONS: More research is required on the topic of sustainable practices in hotels, as their implementation in organizations has been limited to date. However, it generates a competitive advantage for the hotels that apply them, contributing to a sustainable environment. It is concluded that Latin America presents an area of opportunity for developing research on sustainable practices in hotels.
Keywords: sustainability; environmental management; natural resources; tourism.